Analyse de deux quartiers périphériques dans une ville moyenne brésilienne : un double contenu socio-spatial - Vanessa Moura de Lacerda Teixeira (Confins)
The peripheral habitat of contemporary society is a place of socio-spatial inequalities in numerous Brazilian medium-sized cities. Both popular and upper social classes subdivisions are located in the periphery, where the infrastructure is precarious, with little availability of quality public transportation or few commercial and services zones nearby for the inhabitants. This paper proposes to highlight the socio-spatial inequalities in terms of both forms and social contents of two peripheral neighborhoods of a medium-sized Brazilian city. The spatial analysis shows that the distance from the center leads to a change in the daily practices of the inhabitants, especially in their mobility. A reflection about an ongoing process of socio-spatial fragmentation from a preliminary analysis of two peripheral neighborhoods constitutes the result of the article.